(untitled) (REMUNOM, 2025)
In 1991, the economists Grossman and Krueger proposed that the relationship between environmental degradation and economic growth would generate an improvement to the environment, represented by a curve in the shape of an inverted "U", later known as the Environmental Kuznets Curve (CKA). In this context, the objective of this study was to analyze whether a relationship in the format proposed by the authors exists for the state of Pará between the years 2002 and 2018. Thus, two models were developed through the panel data technique, employing Ordinary Least Squares estimations for the fixed effects model in both cases. Model 1 used CO2 emissions as the dependent variable and model 2, deforestation, and in both, GDP per capita was the independent variable. The results found in the first model rule out the possibility of the relationship between the variables being cubic in the time frame chosen for the aforementioned state, indicating the existence of a quadratic curve with upward concavity. In other words, although a reduction in CO2 emission was initially observed, it would grow again after the curve reached its minimum point, in this case equal to R 15,531.70. In the second model, the cubic shape was also not significant, showing a CKA as in the original proposal, in the shape of an inverted "U". Thus, although at the beginning there has been an increase in deforestation caused by the growth in income, upon reaching the maximum point of the curve, equal to R 12,415.44, this same movement of economic growth would be providing a reduction in the deforestation process. In this sense, the results do not give us evidence to infer about the existence of the CKA, at least not in its original format, for the state of Pará between the years 2002 and 2018.